2018
DOI: 10.1002/cpch.41
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic Nucleic Acid (XNA) Synthesis by Phi29 DNA Polymerase

Abstract: Phi29 DNA polymerase (DNAP) is the replicative enzyme of the Bacillus subtilis bacteriophage Phi29. Its extraordinary processivity and its ability to perform isothermal amplification of DNA are central to many molecular biology applications, including high-sensitivity detection and large-scale production of DNA. We present here Phi29 DNAP as an efficient catalyst for the production of various artificial nucleic acids (XNAs) carrying backbone modifications such as 1,5-anhydrohexitol nucleic acid (HNA), 2'-deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…This functional plasticity may be aided by high thermostability, which promotes greater tolerance for mutations that would otherwise be excessively destabilizing. However, A-family [82][83][84][85][86][87][88][89][90] and mesophilic polymerases such as Phi29 [91,92] as well as RNA polymerases [93][94][95][96][97] have also been engineered to accept XNA substrates with success (Table 1). However, the efficiency, fidelity, and kinetics of engineered polymerases on XNA substrates are usually compromised relative to the native enzymes and natural substrates.…”
Section: Polymerase Synthesis Of Xnasmentioning
confidence: 99%
“…This functional plasticity may be aided by high thermostability, which promotes greater tolerance for mutations that would otherwise be excessively destabilizing. However, A-family [82][83][84][85][86][87][88][89][90] and mesophilic polymerases such as Phi29 [91,92] as well as RNA polymerases [93][94][95][96][97] have also been engineered to accept XNA substrates with success (Table 1). However, the efficiency, fidelity, and kinetics of engineered polymerases on XNA substrates are usually compromised relative to the native enzymes and natural substrates.…”
Section: Polymerase Synthesis Of Xnasmentioning
confidence: 99%
“…That is, although some bacteriophages make use of modified nucleobases and have evolved systems that lead to 100% incorporation of the modified bases in their genomes, their DNA polymerases have not specialised towards being able to only incorporate the modified nucleobases-they remain able to recognise unmodified triphosphates. [14][15][16][17][18][19][20][21][22][23][24][25] *Address all correspondence to: vitor.pinheiro@kuleuven.be Still, the increased substrate flexibility of phage DNA polymerases may at least in part justify why a Bacillus subtilis Phi29 DNA polymerase required a single mutation for the synthesis of anhydrohexitol nucleic acids (HNA) [80] while an archaeal enzyme required in excess of seven mutations [81].…”
Section: Xenobiotic Nucleic Acidsmentioning
confidence: 99%
“…If maximum yield is desired, the best solution we have found to date is to purify the XNA (e.g., by PCR purification column or phenol:chloroform extraction and alcohol precipitation) and use the purified XNA as pre-annealed primer:template complex for a polishing reaction using Phi29 DNAP, which will readily extend to the end of templates (at least for HNA) as described elsewhere (Torres and Pinheiro, 2018). If maximum yield is desired, the best solution we have found to date is to purify the XNA (e.g., by PCR purification column or phenol:chloroform extraction and alcohol precipitation) and use the purified XNA as pre-annealed primer:template complex for a polishing reaction using Phi29 DNAP, which will readily extend to the end of templates (at least for HNA) as described elsewhere (Torres and Pinheiro, 2018).…”
Section: Troubleshootingmentioning
confidence: 99%
“…XNA synthesis from mesophilic polymerases (Torres and Pinheiro, 2018), A-family RNA polymerases (Chen et al, 2016;Ghadessy, Ong, & Holliger, 2001) and single-subunit RNA polymerases (Ibach et al, 2013;Sousa & Padilla, 1995) have also been reported.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation